Do Gender Quotas Deliver Substantive Change? Women’s Representation from Islamic Political Parties in Indonesia - Muwahid Muwahid; Moh. Bagus (Faculty of Law, Universitas Sebelas Maret, 2025)
In many countries, women are still treated like second-class citizens when they speak out about politics. This article aims to analyse the implementation of the 30% women's quota by Islamic political parties in East Java, Indonesia, and evaluate its significant effects on the outcomes of the Regional People's Representative Council during the 2019–2024 electoral cycle. This article employs legal research to analyse the implementation of the 30% women's quota by Islamic political parties in East Java, Indonesia, which is widely recognised as a major stronghold of Islamic political parties. The study shows that all political parties, even Islamic ones, have followed the rules and made sure that at least 30% of the candidates for the East Java Regional People's Representative Council from 2019 to 2024 are women. Nonetheless, this numerical representation has not resulted in a significant impact, as just a few regional rules adequately reflect women's interests and rights. This study advances legal scholarship by illustrating that the mere formal adherence to gender quota requirements in electoral law does not inherently result in a substantive gender-responsive law-making process. It thereby enhances socio-legal and feminist legal analysis regarding the disparity between normative compliance and effective legal outcomes in democratic governance